Satisfacción laboral y su incidencia en la productividad de la empresa comandato Quevedo, AÑO 2023 - Fajardo Chávez, Yajaira Estefania (2024)
Job satisfaction represents a fundamental element in the well-being of employees and in the efficient functioning of organizations; a satisfied employee is more productive than one who is not. The main objective of the research is to determine the incidence of job satisfaction on the level of productivity in the Comandato company. The methodology used was exploratory and descriptive, along with inductive, deductive, analytical and synthetic analysis methods. These methods facilitated the exhaustive examination of the study problem and the subsequent obtaining of substantiated conclusions. To collect the necessary information, techniques such as surveys and interviews were used to obtain relevant information about the problem, whose data were then tabulated using data processing tools. This allowed the creation of statistical tables and figures that facilitated the visualization and analysis of the results obtained. The results showed that there is weakness in worker satisfaction due to physical aspects such as poor lighting, inadequate work chairs and the structural part of their workplace, 60% of employees perceive weakness in growth opportunities and professional development, although 70% consider training and development programs positive, the level of institutional productivity grew 7.71% below the goal, which was 15% for the year 2023. Therefore, it is concluded that this issue should be addressed urgently in order to adopt strategies that contribute to job satisfaction, teamwork and this has a short-term effect on productivity levels in the Agency.